FAKTOR PENYEBAB RENDAHNYA LITERASI DI SEKOLAH SMA NEGERI 1 TAPANGO - Saparuddin Saparuddin; Kurnia Kurnia; Nur Hafsah Yunus; Besse Darmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Reading and writing literacy skills are fundamental aspects of learning the Indonesian language. However, many students still struggle with literacy, influenced by various internal and external factors. This study aims to analyze students' literacy levels and the role of teachers in enhancing their literacy skills. The study employs a qualitative approach with a descriptive method. The research subjects are 11th-grade students and Indonesian language teachers at SMA Negeri 1 Tapango in the 2024 academic year. The sampling technique is purposive sampling. Data is collected through questionnaires and interviews, each consisting of 10 questions. Data analysis is conducted quantitatively for the questionnaire results and qualitatively for the interviews through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that 56.25% of students scored below 70, indicating low literacy levels. The primary factors influencing low literacy include a lack of interest in reading, difficulty in understanding texts, as well as limited reading materials and engaging teaching methods. Teachers also face challenges in classroom management and have not received professional training in literacy instruction. To improve students' literacy, it is necessary to implement innovative learning models, enhance teacher competency through training, provide diverse reading materials, and establish sustainable school literacy programs.